A Robust Digital Predistortion Algorithm for 5G MIMO: Modeling a MIMO Scenario With Two Nonlinear MIMO Transmitters Including a Cross-Coupling Effect - Ackermann, Thomas; Potschka, Julian; Maiwald, Tim; Hagelauer, Amelie; Fischer, Georg; Weigel, Robert (IEEE Microwave Magazine, 2020)
Linearity, efficiency, and power consumption are the key figures of merit for modern communication system design as data rates increase toward millimeter-wave communication systems like 5G. A common problem is that both high linearity and efficiency are not simultaneously feasible in power amplifier (PA) design. Hence, when a PA is operated near saturation for highest efficiency, undesired harmonic and intermodulation distortions have to be taken into account. A transceiver comprises several circuit elements, such as a low-noise amplifier, mixer, and PA. In this transceiver chain, the PA usually exhibits the highest power consumption (i.e., it is worthwhile to maximize the efficiency of this circuit component to increase overall system performance).<br
Keywords: digtal-predistortion; power amplifier; DPD; MIMO; Cross-Talk; Linear